PENGUKURAN SUHU PERMUKAAN LAHAN UNTUK PREDIKSI LETUSAN GUNUNG API - Noviar, Heru; Asriningrum, Wikanti; Rijono, Yon (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2006)
Temperature is one of the important parameter for volcano eruption prediction. Remote Sansing Data can be used to measure land surface temperature. The land surface temperature can be calculated with the band 4 and 5 of NOAA Satellite data by implementing the land surface temperature algorithm (LST). From field observation and measurement of volcano Merapi temperature indicate a significant pattern between the creater temperature and the land surface temperature derived from satellite data which shows increasing near eruption.